2006
DOI: 10.1017/s1355770x06003159
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and costs of informal sector pollution control: Mexican brick kilns

Abstract: In developing countries, urban clusters of manufacturers which are "informal"-small-scale, unlicensed and virtually unregulated-can have severe environmental impacts. Yet pollution control efforts have traditionally focused on large industrial sources, in part because the problem is not wellunderstood. This paper presents a benefit-cost analysis of four practical strategies for reducing emissions from traditional brick kilns in Ciudad Juárez, Mexico. To our knowledge, it is the first such analysis of informal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…Despite the low particle emission factors for these kilns, brick making kilns are known to cause locally severe air quality impacts in Mexico as documented by Anderson, who reported PM 10 in homes and an elementary school near brick kilns well above 1000 µg/m 3 . Blackman et al (2006) reported that the 330 brick making kilns in Ciudad Juarez (population 1.2 million) produced 16% of the PM and 43% of the SO 2 in the urban airshed. A large reduction in the total emissions from brick kilns is possible at the regional-national scale by switching to more fuel efficient designs such as the vertical shaft brick kiln (http://www.vsbkindia.org/faq.htm).…”
Section: Brick Making Kilnsmentioning
confidence: 99%
“…Despite the low particle emission factors for these kilns, brick making kilns are known to cause locally severe air quality impacts in Mexico as documented by Anderson, who reported PM 10 in homes and an elementary school near brick kilns well above 1000 µg/m 3 . Blackman et al (2006) reported that the 330 brick making kilns in Ciudad Juarez (population 1.2 million) produced 16% of the PM and 43% of the SO 2 in the urban airshed. A large reduction in the total emissions from brick kilns is possible at the regional-national scale by switching to more fuel efficient designs such as the vertical shaft brick kiln (http://www.vsbkindia.org/faq.htm).…”
Section: Brick Making Kilnsmentioning
confidence: 99%
“…Manufacturing bricks using highly polluting kilns is common not only in Bangladesh but is widespread across India (Bhanarkar et al, 2002;Heierli, 2008;Pangtey et al, 2004), Nepal (Joshi and Dudani, 2008;Raut, 2003), Pakistan (Tahir et al, 2010), China (Lei et al, 2011;Zhang et al, 2007), and even Mexico (Blackman et al, 2006). Brick kilns are an important source of atmospheric black carbon (Reddy and Venkataraman, 2002;Weyant et al, 2014) which contributes disproportionately to global warming and by depositing on Himalayan glaciers reducing reflection of sunlight and increasing glacial melting (Menon et al, 2002;Ramanathan and Carmichael, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Generalizations about the environmental impacts of informal sector might be misleading since several types of small-scale business create fewer environmental problems than vehicular emission or other activities [7]. In contrast, municipal government lacks a clear understanding of the magnitude and incidence of the environmental damages of informal sector [8]. Therefore, studies regarding contribution of informal sector to urban environment must be conducted in regard to set place urban pollution abatement policies.…”
Section: Introduction * * * *mentioning
confidence: 99%